The scientific literature on Posidonia oceanica meadows and related ecosystem services - Capasso, Ludovica; Buonocore, Elvira; Franzese, Pier Paolo; Russo, Giovanni Fulvio (Ecological Questions, 2023)
Posidonia oceanica is an endemic seagrass of the Mediterranean Sea. It has recently raised particular interest for its key role in enhancing climate change mitigation. Actually, P. oceanica is one of the most important marine-coastal ecosystems able to sequester and store considerable quantities of carbon, thus being recognized as a “Coastal Blue Carbon System”. However, due to their coastal position, P. oceanica meadows are often subjected to intense human activities that affect their distribution, health and ecological condition, and the capability of generating ecosystem services, including carbon sequestration and storage. Therefore, it is important to identify strategies to protect P. oceanica meadows, also increasing the awareness on the value of the benefits they generate for human well-being. In this context, environmental accounting tools are much needed to assess the biophysical and economic value of the ecosystem services provided by P. oceanicameadows. In this study we explored the scientific literature on P. oceanica, also investigating the relationships between “Posidonia oceanica” and “Ecosystem Services”. The VOSviewer software was used to create maps based on network data of scientific publications using specific keywords to explore the co-occurrence of different terms connected to the considered research topics. Results showed that the most common keywords in scientific publications on P. oceanica were “Biodiversity”, “Environmental monitoring”, and “Conservation”. The analysis on “Posidonia oceanica” and “Ecosystem Services” showed some gaps in terms of standardized approaches for the ecosystem accounting of P. oceanica meadows. Therefore, further efforts are needed to assess the value of ecosystem services generated by P. oceanica through standardized accounting frameworks making visible its contribution to human well-being at different levels of decision-making processes.